PERADILAN MASA BANI ABBASIYAH - frangky Suleman (Jurnal Ilmiah Al-Syir'ah, 2016)
The judiciary (al-Qadha) is well-known from time immemorial up to the present time. Driven by the need and the welfare of human life, judiciary is something inevitable to exist. It is one of the prerequisites to the establishment of a government in order to resolve disputes between citizens. No political sovereignty in the world, whatever its form, will stand without justice enforcement. Keyword: Al-Qadha, Abbasiyah